Low glucose degradation product peritoneal dialysis regimen is associated with lower plasma EN-RAGE and HMGB-1 proinflammatory ligands of receptor for advanced glycation end products - Opatrna, Sylvie; Popperlova, Anna; Kalousová, Marta; Zima, Tomas (Therapeutic apheresis and dialysis, 2014)
Intraperitoneal glucose degradation products (GDP) load influences systemic advanced glycation end products (AGEs) but the effects on soluble receptor for AGEs (s-RAGE) and its proinflammatory ligands: extracellular newly identified receptor for advanced glycation end-products binding protein(EN-RAGE) and high mobility group box-1 protein (HMGB-1) are unknown. We aimed to compare plasma and peritoneal s-RAGE, EN-RAGE and HMGB-1 between three peritoneal dialysis (PD) prescription regimens with different intraperitoneal GDP loads. High GDP load (glucose-lactate PD fluid, D; N = 8) was compared with a low (glucose-bicarbonate/lactate with icodextrin for overnight dwell, E; N = 9) and a very low GDP load (glucose-bicarbonate/lactate, P; N = 16). D group demonstrated higher plasma EN-RAGE, 77.8 ng/mL, vs. both E, 11.2, P < 0.001 and P, 27.0, P < 0.001 as well as higher plasma HMGB-1, 2.2 ng/mL vs. both E, 1.1, P < 0.01 and P, 1.5, P < 0.01. Plasma s-RAGE, which did not differ between D, E and P, correlated with its effluent levels. Patients with faster peritoneal transport (D/Pcr > 0.65) tended to have higher plasma s-RAGE compared to slow transporters (2300 vs. 1762 pg/mL, P = 0.056). Peritoneal clearance of s-RAGE and EN-RAGE was higher with E compared to both D and P (P < 0.001 resp. P < 0.01). Subgroup of PD patients with CRP above median demonstrated higher plasma HMGB-1 and EN-RAGE, P < 0.05 for both. A lower intraperitoneal GDP load is associated with decreased plasma levels of EN-RAGE and HMGB-1. Peritoneal transport, microinflammation and the capability of icodextrin to increase peritoneal clearance of middle molecular weight substances might also exert an effect on plasma s-RAGE and its proinflammatory ligands levels.
Keywords: biologický transport; Inflammation Mediators; senioři nad 80 let; studie případů a kontrol; peritoneální dialýza; Peritoneum; Glucose; Humans; lidé středního věku; Middle Aged; Aged, 80 and over; Young Adult; Advanced glycation end products; mladý dospělý; Receptor for Advanced Glycation End Products; Glycation End Products, Advanced; Icodextrin; mužské pohlaví; Ligands; glukosa; glukany; receptor pro konečné produkty pokročilé glykace; Biological Transport; Receptor for advanced glycation end products; Extracellular newly identified receptor for advanced glycation end products-binding protein; Peritoneal dialysis; produkty pokročilé glykace; Peritoneal Dialysis; ligandy; Receptors, Immunologic; peritoneum; ženské pohlaví; HMGB1 Protein; icodextrin; Glucans; mediátory zánětu; lidé; Case-Control Studies; High mobility group box-1 protein; Aged; senioři; Male; protein HMGB1; receptory imunologické; Female